The effect of art therapy (drama therapy and music therapy) on increasing the self-confidence of children in speech therapy centers in Isfahan - ashoori, Jamal (International Journal of Education and Cognitive Sciences, 2022)
The aim of this study was to the effect of art therapy (drama therapy and music therapy) on increasing children's self-confidence in speech therapy centers in Isfahan.The research method was quasi-experimental (pre-test-post-test with control group) and the statistical sample was 30 children with stuttering who were selected using available sampling method from speech therapy centers in Isfahan and randomly divided into two equal experimental groups. And controls were divided and tested in twenty sessions.Data collection was done using both library and field methods and the data collection tool was a questionnaire.Data were analyzed using SPSS software. In order to analyze the data, descriptive statistics including mean and standard deviation and inferential statistics including Pearson and Spearman correlation were used. The results of data analysis showed that there is a positive and significant relationship between the use of art therapy (drama therapy and music therapy) and children's self-confidence in speech therapy centers in Isfahan.